2016
DOI: 10.2741/s467
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of colostrum in gastrointestinal diseases

Abstract: 331 ABSTRACTThis paper reviews the composition of colostrum and the potential preventive and therapeutic use of this "first milk" for treating various gastrointestinal disorders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 168 publications
0
21
0
1
Order By: Relevance
“…Overall, the current results strongly suggest that the dietary incorporation of bovine colostrum increased potentially beneficial bacteria in both ileum and colon of piglets. Similarly, other studies have shown that the administration of bovine colostrum, because of its antimicrobial and prebiotic properties, may increase the presence of beneficial microbial populations such as LAB genera and reduce bacteria, such as E. coli , Clostridium , and other potential pathogenic species ( Menchetti et al, 2016 ; Poulsen et al, 2017 ). On the other hand, the effects of the CKTL supplementation on the microbial populations of the large intestine are likely due to the prebiotic and antimicrobial properties of its components.…”
Section: Discussionmentioning
confidence: 90%
“…Overall, the current results strongly suggest that the dietary incorporation of bovine colostrum increased potentially beneficial bacteria in both ileum and colon of piglets. Similarly, other studies have shown that the administration of bovine colostrum, because of its antimicrobial and prebiotic properties, may increase the presence of beneficial microbial populations such as LAB genera and reduce bacteria, such as E. coli , Clostridium , and other potential pathogenic species ( Menchetti et al, 2016 ; Poulsen et al, 2017 ). On the other hand, the effects of the CKTL supplementation on the microbial populations of the large intestine are likely due to the prebiotic and antimicrobial properties of its components.…”
Section: Discussionmentioning
confidence: 90%
“…BC is composed of >250 functional constituents, including immune-stimulating peptides and antimicrobial agents ( 18 , 19 ). Among BC compounds, major ingredients include macronutrients, immunoglobulins, leukocytes, cytokines, growth factors, lactoferrin (LF), lysozyme (LZ), casein, proline-rich polypeptide, glycomacropeptide (GMP), lactalbumin (LA), and enzymes such as lactoperoxidase (LPO) ( Table 1 ).…”
Section: Constituents Of Bovine Colostrummentioning
confidence: 99%
“…Colostrum thus contributes to the development of the immune system in infants as well as facilitates growth, maturation, and repair processes in distinct tissues. Consequently, BC has significantly higher amounts of growth-promoting factors compared with mature milk ( 16 , 18 , 20 ).…”
Section: Constituents Of Bovine Colostrummentioning
confidence: 99%
“…In addition, synergism of the different antimicrobials can be adapted in an attempt to prevent or delay the emergence of resistant populations of the pathogens (Mathur et al, 2017), and our results showed that after fermentation and ultrasonication, BC inhibited MRSA M87fox (established by both methods: inhibition zones and MIC). Bovine colostrum is a safe ingredient since there are no contraindications regarding high dose levels (Menchetti et al, 2016). Reducing the content of pathogenic bacteria is very important for public health because these microorganisms can cause diseases (Özogul and Hamed, 2018).…”
Section: Influence Of Fermentation Ultrasonication and Dehydration mentioning
confidence: 99%